2013
DOI: 10.3390/en6062874
|View full text |Cite
|
Sign up to set email alerts
|

Idle Operation with Low Intake Valve Lift in a Port Fuel Injected Engine

Abstract: Abstract:Reducing fuel consumption is a prime objective in the automotive industry in order to meet regulatory and customer demands. Variable valve actuation offers many opportunities for improving the spark ignition engine's performance in areas such as fuel economy and pollutant emissions. Our studies revealed that the ability to control maximum intake valve lift does indeed offer the ability to control intake air mass, but also has the added benefit that it improves the fuel-air mixing process thanks to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…It determines the interaction between incoming air flow and the fuel jets, as well as the actual space available for spray penetration, given by the position of the piston. Even though liquid velocity is high, air motion plays a significant role in this process, which also needs to be considered in view of ever wider application of variable valves actuation [13,14]. This is also important bearing in mind that injection needs to be advanced during boosted operation at high engine speed [15] in order to maintain the aforementioned compromise between intake air velocity and available spray penetration length [11].…”
Section: Introductionmentioning
confidence: 99%
“…It determines the interaction between incoming air flow and the fuel jets, as well as the actual space available for spray penetration, given by the position of the piston. Even though liquid velocity is high, air motion plays a significant role in this process, which also needs to be considered in view of ever wider application of variable valves actuation [13,14]. This is also important bearing in mind that injection needs to be advanced during boosted operation at high engine speed [15] in order to maintain the aforementioned compromise between intake air velocity and available spray penetration length [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our studies revealed that the ability to control maximum intake valve lift does indeed offer the ability to control intake air mass, but also has the added benefit that it improves the fuel-air mixing process thanks to an increased turbulence, caused by the increased intake flow velocity. This is particularly important at idle and low part loads when low maximum lifts are to be used for improving the fuel economy or for achieving the required power [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the in-cylinder flow field are created by changes in the shape of manifold, valve timing, and type of valve motion. Strategies for optimizing inlet and exhaust valve timings and some of developments in the application of VVT to diesel or gasoline engines can be obtained in some researches [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, negative work decreased by increasing the valve lift. Adrian Clenci et al [5] studied experimentally the effect of low-lift idle operation in a PFI engine on fuel consumption and cyclic variability. They showed that fuel economy and cyclic dispersion improves by using the low-intake valve lift.…”
Section: Introductionmentioning
confidence: 99%